2005
DOI: 10.1002/qua.20887
|View full text |Cite
|
Sign up to set email alerts
|

Computational and experimental studies on the IR spectra and structure of the simplest nitriles (C1 and C2), their anions, and radicals

Abstract: ABSTRACT:The structure and infrared spectra of formonitrile (hydrogen cyanide) and acetonitrile, their anions, and radicals (45 species in all) have been studied by density functional theory (DFT) B3LYP 6-31ϩϩG(d,p) calculations. The results obtained have been compared with the literature and original experimental data. The zero-point vibrational energy (ZPVE)-corrected deprotonation energies of the studied (and other) nitriles correlate fairly well (R ϭ 0.94) with their pK a values, measured in dimethyl sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…The absence of negative frequencies or negative eigenvalues of the second-derivative matrix confirmed that the stationary points correspond to global minima on the PEHS [16]. The use of 6-31ϩϩG(d,p) basis set in DFT computations has recently resulted in better or equally good spectral and structural predictions, compared with other basis sets for both organic molecules and anions [11,12,19,20]. No scaling in the density functional force field was done.…”
Section: Computationsmentioning
confidence: 75%
See 1 more Smart Citation
“…The absence of negative frequencies or negative eigenvalues of the second-derivative matrix confirmed that the stationary points correspond to global minima on the PEHS [16]. The use of 6-31ϩϩG(d,p) basis set in DFT computations has recently resulted in better or equally good spectral and structural predictions, compared with other basis sets for both organic molecules and anions [11,12,19,20]. No scaling in the density functional force field was done.…”
Section: Computationsmentioning
confidence: 75%
“…The charge change values ⌬q i ϭ q i (anion) Ϫ q i (molecule) are usually quite informative in showing the distribution of the new (e.g., carbanionic, azanionic) changes in anions (Refs. [10,11,13,14,19,20,28,29,34] and references therein). According to the present calculations, the new (azanionic) charge of 2a is distributed, as follows: 0.08e Ϫ , 0.23e Ϫ , and 0.12e Ϫ are delocalized over the amino, phenylene, and sulfonyl groups, respectively, and 0.57e Ϫ remain localized at the azanionic center (cf.…”
Section: Electronic Structuresmentioning
confidence: 98%
“…The DMSO as polar aprotic solvent usually de- Table 2. The agreement between the experimental and calculated values is very good -the mean absolute deviation between observed and calculated frequencies is 16.5 cm À1 , which value is not away from the low border of the 15-25 cm À1 interval of deviations, typical for the DFT calculations for molecules containing carbonyl or cyano groups [19][20][21][22][23][24][25][26][27].…”
Section: Infrared Spectramentioning
confidence: 98%
“…Table 1 Total energies (E), Gibbs free energies (G), zero-point vibrational energy (ZPVE) and relative energies (E rel ) of conformers of o-vanillin and its anion. acidities in polar aprotic solvents [19][20][21][22][23][24][25][26] (and references therein): low E D 's high acidities low pK a values.…”
Section: Energy and Conformational Isomersmentioning
confidence: 99%
“…, have been studied widely in nitrile compounds [25][26][27][28][29][30], experimental data about the lowest frequency torsional modes are scarce. For n-propyl cyanide, experimental data have not been reported for the m 30 and m 28 torsional modes.…”
mentioning
confidence: 99%